Development of Blade Pitch Angle Adjustment Device for Small Horizontal Axis Wind Turbine - นิยมวาส, บัญญัติ (Srinakharinwirot University Engineering Journal, 2018)
The objective of this research was to develop a device for adjusting the pitch angle of small horizontal axis wind turbine generators in order that they were functional in different pitch angles as well as solved the problem of one fixed pitch angle. Device has a curve rail, which base of curve rail was attached with the hub of the wind turbine. Wind turbine blades were attached with rail curve of the device, then blade pitch angle could adjust to several degree. Acrylic wind turbine blades was used for this experiment. Wind turbine blade is 70 cm long. The experiment was carried out with the pitch blade angles at 10o, 20o, 30o, 40o, and 50o and the wind velocities at 0 – 9.0 m/s. The study’s result revealed that electric power of wind turbine with acrylic blades which pitch blade angle at 10o and wind velocity at 9.0 m/s was 10.4 W, and electric power of wind turbine with acrylic blades which pitch blade angle at 20o and wind velocity at 9.0 m/s was 12.3 W.